Catalyzing development through ICT adoption : the developing world experience - Kaur, Harleen; Lechman, Ewa; Marszk, Adam (Springer, 2017)
This book examines the role that Information and Communication Technologies (ICTs) play in growth and economic development promotion, specifically for developing countries. It highlights multiple methodologies for quantifying the impact of ICTs. This includes quantitative and qualitative methods, but also novel, conclusive and informative methodological approaches for measuring ICTs influence on economic development. The book highlights trends, perspectives, and success stories for different developing countries. ICTs bring new business models, innovations, capital-labor substitution, improved goods and services to developing markets. Because they can spread rapidly, with little cost and require minimal skills for usage, ICTs create a solid background for social and economic gains. They enable significant reduction in information asymmetries, which improves access to economic activities for multitude of agents, fostering participation, inter alias in labor market of disadvantaged societal groups. After almost two decades of rapid diffusion of ICT in developing world, this book seeks to assess the real benefits and consequences of ICTs adoption in developing countries. The chapters use broad, real-world based evidence to provide a better understanding of the precise nature of new technologies and their impact of the countrỳs economy and society.